The Role of Mindfulness in Improving Focus and Learning Outcomes - Sadia A Ghaffar, Qudsia Nawaz, Zubaida Shaheen, Munnaza Andleeb, Bushra Subuktageen, Junaid Sarfaraz Khan (Pakistan Journal of Medical & Health Sciences, 2024)
In recent years, mindfulness has emerged as a powerful stress-relief tool and improves mental wellness. First practiced in clinical settings, mindfulness is now being used more frequently within schools to enhance the cognitive and emotional functions of students. Focused attention and improved learning outcomes are key areas where mindfulness is being integrated into education. This article review focuses on major aspects of workplace literacy including concentration, emotion regulation, and impact on students’ learning through mindfulness practices.